Conservative political communication : how right-wing media and messaging (re)made American politics - Jarvis, Sharon E., 1969- (New York, NY : Routledge, 2021)
"Conservative Political Communication examines the evolution of appeals, media, and tactics in right-wing media and political communication, tracking trends and shifts from the early days of contemporary conservatism in the 1950s to the Trump administration. The chapters in this edited volume feature the work of senior and junior scholars from the fields of communication, journalism, and political science employing content analytic, experimental, survey, historical, and rhetorical research methodologies. Analyses of the rise of the 24-hour news cycle, the range of partisan news sources, and the role of social media algorithms in political campaigns yield insights for our media and information ecosystems. A key theme across these chapters is how right-wing channels and communications help and hinder partisan fragmentation, a condition whereby novice elected officials create personal conservative brands, appeal to the base through partisan media, and complicate senior leadership's ability to engage in bargaining, compromise, and deal-making. This volume interrogates conservative media and messaging to track where these processes came from, how they functioned in the 2016 United States presidential campaign, and where they may be going in the future. This book will interest scholars and upper-level students of political communication, media and politics, and political science, as well as readers invested in today's political media landscape in the United States"--
Introduction / Sharon E. Jarvis -- Placing media in conservative culture / Matt Grossmann and David A. Hopkins -- Conservatives and race / Michael J. Lee -- Conservatives and party labels / Jacob R. Neiheisel -- Conservatives and the Tea Party / Joshua M. Scacco, David A. Weaver, and Eric C. Wiemer -- Conservative voters vs. Trump supporters / Jay T. Jennings -- Conservatives and women / Lindsey Meeks -- Conservatives and incivility / Ashley Muddiman -- Conservatives and anger / Bryan T. Gervais and Irwin L. Morris -- Conservatives and Twitter bots / Michael W. Kearney -- Conservatives and asymmetric polarization / Annelise Russell -- Conservatives and news feeds / Katherine Haenschen -- Conservatives and misinformation / Jessica R. Collier.
OCLC-licensed vendor bibliographic record.
Keywords: Communication in politics -- United States; Mass media -- Political aspects -- United States; Social media -- Political aspects -- United States; Conservatism -- United States; POLITICAL SCIENCE / Political Ideologies / Conservatism & Liberalism